Investigating the “Feeling Rules” of Generative AI and Imagining Alternative Futures - Andrea Baer (In the Library with the Lead Pipe)
Since the public debut of ChatGPT, the calls for librarians to adopt and promote generative AI technologies and to teach "AI literacy" have become part of everyday work life. For instruction librarians with reservations about GenAI, these calls have become harder to sidestep. Examining discourse on GenAI and AI literacy, I pay attention to messages we hear about the appropriate ways to think and feel about GenAI.